Refugees at Work: Narratives of Identity Construction - Moore, Vikashni (Auckland University of Technology, 2025)
Existing literature has documented identity losses, diminished self-esteem, and employment challenges among refugees while also revealing the importance of their work integration in resettlement societies. However, we have only a limited understanding of how refugees actively negotiate and potentially transform their identities through diverse forms of work. Furthermore, in the contexts of identity and work, scholarship usually focuses on single aspects of the migration journey. This thesis explores the complex processes of identity construction among refugees through the research question – How are refugees’ identities constructed throughout their migration journey in the context of work? Guided by a constructivist grounded theory methodology integrated with the translocational positionality framework, I collected and analysed data from 41 participants across three groups in Aotearoa New Zealand – 22 refugees, 11 managers and mentors (M&Ms), and eight pathways-to-work providers (PWPs) – in a way that privileged participants’ voices while emphasising the co-construction of knowledge. Five significant findings emerged from analysis of the data collected from the refugee participants. The migration journey emerged as the contextual framework for understanding identity construction, encompassing refugees’ past, present, and future. Three primary identity constructs – anchors, refugeehood, and place – were found to be influential in the formation of identities for refugees. An insider-outsider continuum was a site for identity constructions, representing a dynamic process of negotiating multiple social positions. Refugees’ resourcefulness materialised through four interconnected strategies of exercising agency, demonstrating self-efficacy, finding alternative pathways, and remaining undeterred. Finally, the meaning of work, connecting intrinsically to identity constructions throughout the migration journey, was revealed in four themes of being oneself and to be more, working for survival, working for family, and working for communities, explaining why refugees chose to work in the roles that they do. Findings from the interviews with M&Ms and PWPs revealed five distinct motives driving their refugee assistance. Empathy was found to be a key motive, in addition to economic value, job or organisational requirement, a moral imperative, and personal fulfilment. Five key dimensions of work integration were identified – access to work, capabilities development, changing narratives, finding meaning in work, and social and cultural integration facilitation. Finally, the concept of a metaphorical stepping stone as a provisional meaning of work component also emerged as a finding from these two participant cohorts. From the above findings, this thesis presents a new theory on the bidirectional relationship between refugees’ identity and their meaning of work constructions. It contributes to reconfiguring understandings of the dialectic between the socially constructed ‘Me’ and the agentic ‘I’ in the migration journey and work contexts. The novel theory proposes a fluid identity construction process while highlighting the interplay between identity constructs and work meanings. Refugees’ resourcefulness throughout their migration journey, alongside strategies utilised by M&Ms and PWPs, influence identity formation and work meanings, and this led to the development of a new relational work integration framework. This research advances scholarship across disciplines – forced displacement and refugee resettlement studies, organisational behaviour, the meaning of work, and sociological and social psychology – and informs resettlement policy enhancement. It reconceptualises work integration beyond traditional employment pathways. The framework developed in this thesis is attentive to refugees’ unique experiences in constructing meanings from work. It contributes to refugee studies through a holistic migration journey perspective that also conceptualises refugeehood as an intricate, fluid construct incorporating agency. This thesis demonstrates how an ecosystem of employers and resettlement services organisations can provide meaningful work while supporting refugees’ identity formations and recommends policy improvements requiring coordination across individual, organisational and government levels.